Air Laut Dalam Perspektif Hadis Dan Sains: Analisis Makna Ṭahuūr Dan Relevansinya Dengan Kimia - Muklihah Muklihah; Hikmatul Izzah; Qurrotu A’yun (LPPM IAI Hasanuddin Pare-Kediri, 2025)
Abstract: This study aims to examine the hadith of the Prophet Muhammad (peace be upon him) about the purity of seawater from the perspective of hadith and modern science, especially regarding the meaning of ṭahūr (holy and purifying) and the content of chemical elements of seawater. The hadith that became the object of study was the words of the Prophet (peace and blessings of Allaah be upon him):